MATHEMATICAL METHODS FOR EVALUATION OF WEBOMETRIC INDICATORS OF INFORMATION LIBRARY CENTERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Nowadays, new technologies are being used in every aspect of our lives. In particular, public libraries are focusing on attracting readers and introducing new services through the use of various new technologies. Therefore, providing information to users through public library websites, studying data on the duration of website use, the number of visits, determining the purposes of users' visits, and evaluating their visits are among the pressing issues of today. The purpose of this research is to analyze the websites of public libraries operating in the library sector, and to improve the efficiency of the system to provide quick and quality remote services to users. The article proposes a system for determining webometric indicators of public library websites, coefficients for evaluating the system, comprehensive mathematical methods for multi-criteria evaluation of websites. As part of the study, a method and mathematical solutions for expert evaluation of websites using the rating method are proposed. In particular, the proposed methods for multi-criteria evaluation of library websites were tested by special experts on the example of 14 websites belonging to the same category. Based on the studied criteria, webometric indicators were summarized, and based on the analysis conducted, the data were processed and the evaluation coefficient of the system for determining webometric indicators of library websites was calculated. Having obtained these results, it is possible to rank library websites. The essence of this method is that using this method, we can not only evaluate a website in a traditional way, but also obtain the following useful results: a complete evaluation of websites, an evaluation of websites according to certain criteria, and a comparison of website ratings. In general, evaluating public library websites is necessary not only to determine the popularity of libraries, but also to make sound management decisions, as well as to identify the needs and interests of readers.